In situ and micro‐Raman spectroscopy for the identification of natural Sicilian zeolites. (10th November 2021) - Finocchiaro, Claudio; Coccato, Alessia; Barone, Germana; Bersani, Danilo; Culka, Adam; Fornasini, Laura; Mazzoleni, Paolo; Jehlička, Jan; Rousaki, Anastasia; Vandenabeele, Peter
Abstract: Zeolites are present in numerous outcrops of volcanites of different ages in Sicily (Italy). Some of these outcrops are important because they constitute the ideal genesis conditions of some of these minerals, which represent geological indicators of chemical and geothermal gradients involved during their formation. For this purpose, a group of zeolites coming from areas of the Ionian coast and Palagonia village (Eastern Sicily) was investigated by means of Raman spectroscopy. In the geological record, these areas have been influenced by intense volcanic events that produced mineralization of hydrothermal origin. Sicilian zeolite samples were analysed in situ using different mobile Raman apparatus, directly on the outcrops of Aci Castello and the nearby Lachea Island, or in local collections where they are preserved. Some of these samples have been then analysed using laboratory micro‐Raman to compare the results and identify the zeolite types. The strength and weakness points of each instrument have been highlighted. Often, the Raman spectra of zeolites are affected by broad fluorescence, making them of difficult interpretation. However, satisfying results were obtained with portable devices, whose identifications were confirmed by micro‐Raman, discerning zeolites of different groups, such as analcime, chabazite, natrolite and phillipsite. The use of portable instruments has demonstrated the possibility to obtain identification of zeolites and related minerals both on site and in the laboratory, whose results match with the geological setting of the considered areas. Abstract : Samples of Sicilian zeolites (i.e., analcime, chabazite, natrolite and phillipsite) from a private collection were tested with portable and fixed Raman spectrometers, equipped with 532‐ and 785‐nm laser sources. Local outcrops on the Eastern Sicilian coast are also tested with portable devices. The high wavenumber region, excited by a green laser, proved extremely interesting for the distinction among different zeolites, with similar results obtained in the laboratory and on the field.